Experiences with rituximab for the treatment of autoimmune diseases with ocular involvement - Pelegrin, Laura; Jakob, Eva; Schmidt-Bacher, Annette; Schwenger, Vedat; Becker, Matthias; Max, Regina; Lorenz, Hanns-Martin; Mackensen, Friederike (The journal of rheumatology, 2014)
Objective. To report the efficacy of rituximab (RTX) in the treatment of ocular or orbital inflammation accompanying autoimmune diseases refractory to previous standard immunosuppressive therapy. - Methods. We reviewed medical records of 9 consecutive patients with noninfectious ocular or orbital inflammation treated with RTX. - Results. Over a mean followup of 42 months, 7 patients were in clinical remission, 1 had partial response to treatment, and 1 did not respond. Best corrected visual acuity improved ≥ 1 line in 4 patients, was stable in another 4 patients, and worsened in 1. Concomitant immunosuppressive therapy was tapered in 6 cases. Systemic corticosteroids were tapered or kept below 7.5 mg a day in 5 patients 1 year after the first RTX cycle. - Conclusion. RTX therapy, in patients who are refractory to standard immunosuppressive therapy, was effective and showed a beneficial response to treatment including induction of clinical remission of inflammation in most patients.
First Release: Nov 15, 2013
Gesehen am 03.11.2020